ASSOCIATION OF CC16 POLYMORPHISM WITH RISK FACTORS OF FORMATION OF BRONCHO-OBSTRUCTIVE SYNDROME IN CHILDREN - E N Seliverstova (RUDN Journal of Medicine, 2018)
Syndrome of bronchial obstruction is a symptomatic complex arising on the background of constriction or occlusion of bronchial tubes of different caliber due to bronchospasm, edema and inflammation of the bronchial mucosa, hypersecretion of mucus or compression by surrounding structures. Bronchoobstructive syndrome (BOS) is one of the most common pathological conditions in pediatric practice. The outcome of BOS can be different: from the complete disappearance of clinical manifestations to the process, disability or even death. Accordingly, the study of this problem and the search for methods for early diagnosis and prediction of the outcome of BOS is a very urgent problem. In order to identify risk factors for BOS and to clarify the association with polymorphism of the CC16 gene, 126 children belonging to the main group and 58 from the comparison group were examined. In the course of the study, the triggers influence on the formation of the BOS of concomitant ENT pathology, burdened personal and family allergic anamnesis, and also the recurrent nature of respiratory infections in the first year of life was proved. The association of polymorphism of AA gene of CC16 with the presence of weighed allergic anamnesis and frequent episodes of ARVI, as well as the influence of this genotype on the early debut of respiratory diseases in children, has been revealed. The relationship of the GG genotype with the concomitant ENT pathology among patients with recurrent BOS has been proved.